Characteristics of Population in the Valley Districts of Manipur, India - Golson, Ningthoujam; Singh, Kh. Pradipkumar (National Geographical Journal of India, 2022)
The valley districts of Manipur are the most densely populated areas in the North-East India. Due to its physiography and central position, majority of the population in Manipur concentrate in the valley districts. Despite its one-tenth of the total geographical area of Manipur, the valley district of Manipur supports more than half of the state's population. The main thrust of the paper is on the size, growth and distribution of the population in the valley districts of Manipur. The data collected from the Census of India is used in calculating and analysing the problems. Various cartographic techniques have been employed to show the population growth, density, sex ratio, composition of workers, ete. for the period of 1951- 2011. The paper also compares the growth rate of Manipur with respect to valley district of Manipur. An annual exponential rate is used for computing future trends of population.